Social Capital of Left-Behind Children: Determinants and Association With School Performance - Tolentino, Melanie P. (Animo Repository, 2018)
This study examined the influence of social capital on the school performance of left-behind children who were deprived of the physical presence of migrant parents. Social capital in the family, in school, and the community were examined through quantitative design. A survey was conducted among 384 left-behind children selected through multi-stage probability sampling. Results of regression analysis showed that higher levels of shared values and emotions in the family, social trust in the school, involvement in community life, and age of migrant parents determine a higher level of values learned. Higher levels of supportive relationship, social trust at school, and involvement in community life predict a higher level of right conduct. Higher levels of supportive relationship and supportive norms determine a higher average grade. Left-behind children with mother-present, father migrant draw more social capital in the family; while left-behind children with father-present, mother-migrant generate social capital in the school and the community. It is recommended that fathers should be involved in providing care and in the nurturing of left-behind children. Schools should cultivate an environment that invests in social capital especially for the left-behind children lacking in social capital at home. Government institutions serving for the welfare of migrant parents should educate and assist in the psycho-social needs of left-behind children and migrants’ households.